PENGARUH PENGGUNAAN MINERAL LEMPUNG DENGAN PENAMBAHAN BAHAN ADITIF TSG 107 + Pb3O4 DALAM PEMBUATAN KERAMIK UNTUK IMMOBILISASI SLUDGE CaCO3 YANG MENGANDUNG CESIUM - -, Basuki (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
Industry using radioactive agent of cesium will result of radioactive waste. The waste may be liquid or solid waste. When it is disposed to environment, it will be very harmful for human being and other living creatures. The objective of this research was to study effect of clay mineral for immobilization of CaCO3 waste as ceramic material, using absorption test, press test and leaching test.Method used is weight of 300 grams mix of ceramic material consisting of 80% base mineral composition (kaolin, 60%; feldspar 15%; clay, 5%). Waste of CaCO3 consisting cesium with variation of 5%, 10%, 15%, 20% and 25%. Additions of additive substance were 2%, 4%, 6%, 8% and 10%. Water varieties were 45, 5%, 6%, 8%, and 10% weight.Result of the research indicated that composition of base mineral making ceramic, addition of CaCO3 waste containing cesium and addition of additive influence heavily on velocity of leaching of ceramic monolith. Greater CaCO3 addition and additive addition caused lower leaching velocity. It was indicated with 5% to 15% CaCO3 addition, velocity decreased from 549.378 x10-6gram.cm-2.day-1 to 74.665x10-6gram.cm-2.day-1. Greater addition of CaCO3 result in lower density of ceramic monolith block as result from heating at 10000C, but weight decrease was greater. Water release in heating process led to holes in ceramic monolith block that would reduce its stress strength. In conclusion, amount of ceramic-making base mineral composition, CaCO3 waste, and additive addition affect density, weight decrease pre-and post-heating at 10000C, absorption level, stress strength and leaching velocity.